Nutrient Regulation of Endocrine Factors Influencing Feeding and Growth in Fish - Bertucci, Juan Ignacio; Blanco, Ayelén Melisa; Sundarrajan, Lakshminarasimhan; Rajeswari, Jithine Jayakumar; Velasco, Cristina; Unniappan, Suraj (Frontiers in Endocrinology, 2019)
Endocrine factors regulate metabolism and growth, two interlinked physiological processes critical for the proper development of organisms. Somatic growth is mainly regulated by growth hormone (GH) and insulin-like growth factors I and II (IGF-I and IGF-II) that act in target tissues, including muscle and bones. Metabolism is mainly regulated by peptidyl hormones, which act both centrally and/or peripherally to maintain energy balance. While there seems to be two separate systems regulating somatic growth and metabolism, both are interrelated. The GH-IGF axis, and hormones regulating metabolism are regulated by both internal (indicating metabolic status of the organism) and external (environmental) signals. Among the external signals, one of the most notable are diet availability and diet composition. Macronutrients and micronutrients act on several hormone-producing tissues to regulate the synthesis and secretion of metabolic hormones, and hormones of the GH-IGF axis, eventually modulating growth and energy balance. A comprehensive understanding of how nutrients regulate hormones is essential to design diet formulations that better modulate endogenous factors for the benefit of aquaculture to increase yield. This review will discuss the current knowledge on nutritional regulation of hormones modulating growth and metabolism in fish.